Lycopene - tomato's secret weapon against oxidative stress (Bangladesh Journal of Medical Science, 2012)
Back ground: Lycopene, 40 carbon acyclic carotenoid containing 11 conjugated double bonds, is a phytochemical found in tomatoes and other red fruits. Oxygen derived free radicals are the most reactive species and as an antioxidant lycopene has a singlet oxygen quenching ability twice as high as that of ?-carotene and 10 times higher that of ?-tocoferol, lycopene participate in a host of chemical reactions to protect critical cellular biomolecules including lipid, proteins and DNA. Materials and Methods: The present study include 30 subjects having oxidative stress, age between 40-60 years, nonsmoker, with no history of chronic systemic illness and no medication were taken as patients.30 patients matched healthy subjects were taken as control. All subjects were selected from outpatient department of NSCB Medical College Jabalpur M.P. After estimation of base line antioxidant enzyme and vitamins, we supplement 180 gm of tomato (products like soup, paste. ketchup) contain 12 mg of lycopene to the patient group. After 60 days of lycopene supplementation oxidative stress biomarkers like SOD, GPX, GR, GSH, lipid peroxidation product MDA and other antioxidant vitamins A, vitamin C, vitamin E were estimated in patient's blood sample. Results: The main result of the study revealed that lipid per oxidation product MDA was found to be decreased significantly but after lycopene supplementation levels were improved. The results of SOD , GPX, GR, GSH,Vitamin A ,Vitamin E and Vitamin C were significantly increased after lycopene supplementation, it indicates the improved antioxidant profile after the supplementation of lycopene. Conclusion: There was a significant decrease in oxidative stress after the supplementation of lycopene therefore the study suggest that body's internal production of antioxidant is not enough to neutralize all free radicals, so increased dietary intake of antioxidant lycopene in the form of tomato products is beneficial, which is easily available in developing country like India. Key Words: Oxidative stress; Lycopene; MDA; GSH; SOD; Vitamin C; Vitamin E DOI: http://dx.doi.org/10.3329/bjms.v10i4.9500 BJMS 2011; 10 (4): 275-279